Feed additives for swine: Fact sheets – carcass modifiers, carbohydrate-degrading enzymes and proteases, and anthelmintics - J Y Jacela; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; David G Renter; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2009)
There is increasing consumer demand for leaner and healthier pork products. Improvements in genetics, new technologies, and increased understanding of nutrition have become instrumental in helping producers meet this demand. Continued research also has led to the development of products that can be included in swine diets as carcass modifiers. A dietary carcass modifier is broadly defined as any component of the diet that alters the resulting carcass composition of pigs. Generally, the mechanism of action of carcass modifiers is aimed at increasing protein and muscle deposition while reducing fat deposition. These products vary in the mechanisms by which they modify carcass quality. In addition, not all carcass modifiers are approved for use in pig diets, for public-health reasons. Understanding the modes of action and differences between these products is important for safe and effective use.; Journal of Swine Health and Production; 17; Swine Day, 2009, Kansas State University, Manhattan, KS, November 19, 2009
Keywords: http://www.aasv.org/shap.html; Swine; Carcass modifiers; Carbohydrate-degrading enzymes and proteases; Anthelmintics; Ractopamine HCl